High salt intake damages myocardial viability and induces cardiac remodeling via chronic inflammation in the elderly - Li, Ke; Song, Huajing; Wei, Fang; Liu, Di; Zhao, Yingxin; Yin, Haipeng; Cui, Yi; Zhang, Hua; Liu, Zhendong (Frontiers in Cardiovascular Medicine, 2022)
Background: The heart is an important target organ for the harmful effects of high dietary salt intake. However, the effects and associations of high salt intake on myocardial viability, cardiac function changes, and myocardial remodeling are unclear. Methods: A total of 3810 participants aged 60 years and older were eligible and enrolled from April 2008 to November 2010 and from August 2019 to November 2019 in the Shandong area of China. Salt intake was estimated using 24-h urine collection consecutively for 7 days. Myocardial strain rates, cardiac function and structure, and serum high-sensitivity C-reactive protein (hsCRP) levels were assessed. Participants were classified into low (n = 643), mild (n = 989), moderate (n = 1245), and high (n = 933) groups, corresponding to < 6, 6–9, 9–12, and > 12 g/day of salt intake, respectively, depending on the salt intake estimation. Results: The global early diastolic strain rate (SRe) and late diastolic strain rate (SRa) in the high group were 1.58 ± 0.26, 1.38 ± 0.24. respectively, and significantly lower compared with the low, mild, and moderate groups (all P <0.05). The global systolic strain rate (SRs) in the high group was -1.24 ± 0.24, and it was higher than those in the low, mild, and moderate groups (all P < 0.05). Salt intake was independently and positively correlated with global SRs, Tei index, and the parameters of left ventricular structure separately; negatively correlated with global SRe and SRa, left ventricular short axis shortening rate, left ventricular ejection fraction after adjusting for confounders (all Padjusted < 0.001). Hayes process analyses demonstrated that the mediating effects of hsCRP on global SRe, SRa, and SRs; Tei index; and left ventricular remodeling index were -0.013 (95% CI: -0.015–-0.010), -0.010 (-0.012–-0.008), 0.008 (0.006–0.010), 0.005 (0.003–0.006), and 0.010 (0.009–0.012), respectively (all Padjusted < 0.001). Conclusion: Our data indicate that excess salt intake is independently associated with the impairment in myocardial viability and cardiac function, as well as myocardial remodeling. Chronic inflammation might play a mediating role in the association between high salt intake and cardiac function damage and myocardial remodeling.